MANAGING THE STATE OF «ECONOMIC SECURITY» OF AGRICULTURAL ENTERPRISES IN TERMS OF RESOURCE CONSTRAINTS AND DIVERSIFICATION OF AGRICULTURAL PRODUCTION - Іванько, А. В.; Ксенофонтов, М. М. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
Completed meaningful clarification of the essence of the concept of "management of the state of economic security of agricultural enterprises". The main functional components of the economic security of agricultural enterprises are established: institutional, financial, technical and technological, personnel, environmental, informational and guard. The algorithm of management of the level of economic security of agricultural enterprises is determined: definition of economically safe state of the enterprise; factors influencing it and the order of actions to maintain the enterprise in the desirable economically safe condition in the course of economic activity. The emphasis is placed on the need to take into account in the management of the state of the economic security of enterprises the factor of resource constraints and opportunities for diversification of agricultural production. There are two angles of limited resources: general and individual enterprises. At the same time, the overall perspective is considered in the context the ratio of resource constraints to the unlimited needs of society, coming from properties of the rarity of resources and the need of market players for them to compete for their own economic activity. The second type of resource constraints is considered in the context of the limited possibilities of state support for agricultural enterprises. It is proved that ensuring the proper level of economic security of enterprises depends on the results of economic activity, the effectiveness of which can be increased through operational, investment and financial diversification